Crossing the line: K-12 public school teacher negotiation of unsolicited requests for self-disclosure - Moreland, Emily Susan, author; Griffin, Cindy, advisor; Sprain, Leah, advisor; Aragon, Antonette, committee member (Colorado State University. Libraries, 2011)
In the K-12 public school classroom, members of the public may interpret personal information shared by an instructor with his or her students as indoctrinating or persuasive. Using Petronio's (2002) theory of Communication Privacy Management, this thesis sought to expand self-disclosure research by applying it to the public school classroom. Building on Zhang's (2007) study of the uses of instructor self-disclosure in the K-12 public school classroom, this thesis was organized around the following research questions: RQ1: What communicative strategies are used by K-12 public school teachers to respond to unsolicited requests for self-disclosure by their students? RQ2: How does teacher preparation affect a K-12 public school teacher's decision to either share or keep private personal information in the classroom? RQ3: What do teachers perceive to be the benefits and drawbacks of using self-disclosure in the K-12 public school classroom? RQ4: What rules govern these moments of unsolicited requests for self-disclosure? Where do these rules originate? In order to address these questions, 46 public school teachers across the country were recruited to complete a five-part online survey that asked them reflect on their own experiences using self-disclosure in their classrooms. The data gathered from this study suggest that privacy rules are closely tied to public notions of appropriateness, which are impacted by normative beliefs about who teaches America's students and what the nature and purpose of teaching is in America. In addition to the broad findings of the study, specific communicative strategies used by teachers when dealing with unsolicited student requests for private information were identified, as well as topic avoidance strategies used when a teacher wished to avoid answering a student's question. The main communicative strategies utilized by teachers in this study were direct strategies including the use of short and simple responses, indirect strategies, or redirection strategies, such as turning the question into a teachable moment. Topic avoidance strategies included many of these same strategies, as well as the use of humor or sarcasm. The benefits of self-disclosure as perceived by teachers are also discussed in this thesis and include reciprocity, improved communication with students, and feelings of closeness with students. Teachers also frequently cited the benefit of "having my students see me as a real person" on the survey. Drawbacks included risks to security, stigma, face, and role. Consequently, many of the teachers surveyed practiced self-policing of their conversations with students. It is argued in this thesis that self-silencing can cause some teachers, particularly those whose beliefs and lifestyles exist outside of the mainstream, to miss out on positive personal and professional outcomes tied to self-disclosure. Therefore, suggestions for how teacher education programs can better prepare preservice teachers to effectively handle student requests for private information are discussed, as well as suggestions for further research.
Keywords: communicative strategies; K-12; communication privacy management theory; public school teacher; self-disclosure; topic avoidance strategies